METAPHORISATION OF BREXIT IN MODERN POLITICAL DISCOURSE - Olha Bilyk; Nataliia Pyliachyk (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2018)
The article deals with an interdisciplinary perspective to a political discourse presenting conceptual metaphors as a powerful and effective means for conceptualising life experience of modern society. The focus of the study is on the analysis of topics of intense interest in the political communications and especially the mass media which is considered to be in the centre of political continuum. The research presupposes the analysis the conceptual metaphors which are built up on mappings concerning such source domains as HUMAN BEING, NATURAL PHENOMENON, DISEASE that provides a way to structure target domain of the concept BREXIT. Being produced by world politicians and political journalists these conceptual metaphors are both directly and indirectly aimed at distributing political power on perceiving and understanding such a concept as BREXIT. Under the Conceptual metaphor theory framework, this paper discusses the dynamic and flexible features of such metaphors as BREXIT IS A HUMAN BEING, BREXIT IS A NATURAL PHENOMENON, and BREXIT IS A DISEASE which can influence the audience and transform themselves into one of the effective tools of conceptualisation of reality. Of special interest is the mapping which is viewed as the sets of systematic correspondences between the source and the target domains.